Peranan Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S) â€œSahabat Taniâ€ Dalam Meningkatkan Produktivitas dan Pendapatan Petani Bunga Potong Krisan di Kelurahan Kakaskasen Satu dan Dua - Brainhard M. Kereh; Welson M. Wangke; Tommy F. Lolowang; Juliana R. Mandei (COCOS, 2015)
ABSTRACTThe objective of this research is to determine differences in productivity and farmers income cut flower chrysanthemum training and who do not follow P4S training. The results showed the productivity and income of chrysanthemum cut flower growers who follow P4S greater than the chrysanthemum cut flower growers who do not follow P4S, is the average productivity of cut flower growers who follow P4S amounted to 43.44 stalk while farmers who do not follow P4S at 37.51 stalk and the average income of farming chrysanthemums at the farmers who follow P4S with a land area of 1000m2 Rp. 85.676.071.37 while farmers who do not follow P4S Rp. 67.913.685.99.From the results obtained, this training center P4S succeeded in giving instruction to farmers. Evident from the productivity and income of farmers cut chrysanthemum flowers that follow P4S greater than chrysanthemum cut flower growers who do not follow the P4S.